DATABASE SYSTEMS : Design, Implementation, and Management - Coronel, Carlos; Morris, Steven (Steven A.) (Cengage Learning, 2019)
"Provide a balanced approach to databases as the market-leading DATABASE SYSTEMS: DESIGN, IMPLEMENTATION, and MANAGEMENT, 13E emphasizes the knowledge and skills necessary for success and makes databases accessible without overwhelming students. Readers gain a solid foundation in database design and implementation as diagrams, illustrations, and tables clarify in-depth coverage of database design. Students learn how successful database implementation involves designing databases to fit within a larger strategic data environment. Revised coverage of SQL introduces more examples and simpler explanations that focus on areas most important for a database career -- making supplementary SQL materials unnecessary. Additional coverage of Big Data Analytics and NoSQL, including related Hadoop technologies, offers a strong hands-on approach. MindTap® now include a digital auto-graded MySQL environment." -- Publisher